Analisis Peran Promosi Terhadap Perkembangan Jumlah Nasabah Di Bank Syariah Indonesia Kc Bojonegoro - Damar Septian (Genius: Jurnal Ekonomi Dan Manajemen, 2024)
Growth in the number of customers is the main indicator of the success of the banking industry, including Islamic banking, which faces challenges in increasing competitiveness amid the dominance of conventional banking. An effective promotional strategy is one of the key factors in attracting new customers and maintaining the loyalty of existing customers. This study aims to analyse the effectiveness of the promotion mix in increasing the number of customers at PT Bank Syariah Indonesia KC Bojonegoro.This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews with marketing managers and promotional staff, direct observation of promotional activities, and document analysis related to the number of customers and promotional costs. The results showed that PT Bank Syariah Indonesia KC Bojonegoro implemented several promotional strategies, namely advertising through print and digital media, personal selling involving marketers in providing education to prospective customers, sales promotion in the form of loyalty prizes, and publicity through news and social media. From the analysis of customer growth trends, it can be seen that the promotional strategies implemented succeeded in significantly increasing the number of customers, where there was an increase from 7 million customers in February to 19 million customers in August. In addition, the increase in promotional budget also contributed to the increase in the number of customers. This research confirms that the right combination of promotional strategies can increase the attractiveness and public trust in Islamic banking.